2008
DOI: 10.1038/sj.bjc.6604302
|View full text |Cite
|
Sign up to set email alerts
|

Work ability and return-to-work in cancer patients

Abstract: The extent to which self-assessed work ability collected during treatment can predict return-to-work in cancer patients is unknown. In this prospective study, we consecutively included employed cancer patients who underwent treatment with curative intent at 6 months following the first day of sick leave. Work ability data (scores 0 -10), clinical and sociodemographic data were collected at 6 months, while return-to-work was measured at 6, 12 and 18 months. Most of the 195 patients had been diagnosed with breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
239
4
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(274 citation statements)
references
References 29 publications
13
239
4
10
Order By: Relevance
“…In our study, the employment rate was 76% on average 23 months after diagnosis and considerably higher compared to findings showing that overall, about 63.5% of cancer patients (range 24-94%) manage to return to work (17). However, comparable results (73%, range 64-82%) have been found at 18 months after the cancer diagnosis among breast cancer patients (14) and among samples with mixed tumor entities (1,8,25). Concordant with previous studies showing work changes in 8-17% of cancer survivors, we found similar results (25,30).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In our study, the employment rate was 76% on average 23 months after diagnosis and considerably higher compared to findings showing that overall, about 63.5% of cancer patients (range 24-94%) manage to return to work (17). However, comparable results (73%, range 64-82%) have been found at 18 months after the cancer diagnosis among breast cancer patients (14) and among samples with mixed tumor entities (1,8,25). Concordant with previous studies showing work changes in 8-17% of cancer survivors, we found similar results (25,30).…”
Section: Discussioncontrasting
confidence: 39%
“…Since an increasing number of patients are likely to return to work after diagnosis and treatment completion, there is an increasing recognition of the short and long-term impact of cancer and both its physical and psychosocial consequences on employment during the last years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Unfavorable cancer and treatment consequences include a variety of physical and functional disabilities, and psychological distress that may adversely affect a patient's work ability, work satisfaction, as well as employment status (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Several preceding studies explored the relationship between work ability and work-related outcomes in cancer survivors. For example, de Boer et al (2008) concluded in a prospective study that self-assessed work ability is an important factor in the RTW process of cancer survivors, independent of age and clinical factors [38]. Also, B€ ottcher et al (2013) found that limited self-assessed work ability increases the probability of not returning to work [39].…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…Using regression analysis based on self-report questionnaires or administrative data, many previous studies have shown that several factors can enhance or hinder the return to work (RTW) of cancer survivors (3,(7)(8)(9)(10)(11). However, the difficulties of managing work depend on a complex interaction of individual and environmental factors and the social security system (4,12), and these difficulties may change during the course of the disease.…”
mentioning
confidence: 99%